2019
DOI: 10.1111/apha.13356
|View full text |Cite
|
Sign up to set email alerts
|

Roles of lncRNAs and circRNAs in regulating skeletal muscle development

Abstract: The multistep biological process of myogenesis is regulated by a variety of myoblast regulators, such as myogenic differentiation antigen, myogenin, myogenic regulatory factor, myocyte enhancer factor2A-D and myosin heavy chain. Proliferation and differentiation during skeletal muscle myogenesis contribute to the physiological function of muscles. Certain non-coding RNAs, including long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs), are involved in the regulation of muscle development, and the aberran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 109 publications
(199 reference statements)
0
25
0
Order By: Relevance
“…8,9 Accumulating evidences about circRNAs have demonstrated that they can impact diverse biological processes and are also implicated in tumour generation and development. [10][11][12] The most investigated function of cir-cRNAs is as master regulators of gene expression that act to sequester or 'sponge' other gene expression regulators, such as miRNAs. 13,14 For instance, recent studies have indicated that circIFT80 functions as a competing endogenous RNA (ceRNA) of miR-1236-3p to promote the development of colorectal cancer.…”
Section: Circular Rnas (Circrnas) Are a Class Of Non-coding Rnas (Ncrmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Accumulating evidences about circRNAs have demonstrated that they can impact diverse biological processes and are also implicated in tumour generation and development. [10][11][12] The most investigated function of cir-cRNAs is as master regulators of gene expression that act to sequester or 'sponge' other gene expression regulators, such as miRNAs. 13,14 For instance, recent studies have indicated that circIFT80 functions as a competing endogenous RNA (ceRNA) of miR-1236-3p to promote the development of colorectal cancer.…”
Section: Circular Rnas (Circrnas) Are a Class Of Non-coding Rnas (Ncrmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a class of non‐coding RNAs (ncRNAs) with limited ability to encode proteins and usually form a closed circular structure covalently joined by the 3′ and 5′ ends 8,9 . Accumulating evidences about circRNAs have demonstrated that they can impact diverse biological processes and are also implicated in tumour generation and development 10‐12 . The most investigated function of circRNAs is as master regulators of gene expression that act to sequester or ‘sponge’ other gene expression regulators, such as miRNAs 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs are expressed in several different organs following a spatial-and temporal-specific course, which suggests their potential biofunctions (Chen and Schuman, 2016;Zhao W. et al, 2019). To date, there is a growing number of studies reporting that circRNAs could be involved in the development of mammalian tissues as in neural development (van Rossum et al, 2016;Constantin, 2018), in osteogenic differentiation (Gu et al, 2017;Huang et al, 2019), in skeletal muscle development (Chen et al, 2020) or in hematopoiesis (Bonizzato et al, 2016).…”
Section: Circrnas In Cell Differentiationmentioning
confidence: 99%
“…Accumulating evidence have shown that lncRNAs are key regulators involved in numerous important biological processes including stem cell maintenance and differentiation, myogenesis, and adipogenesis in particular [ 11 ]. Recently, numbers of lncRNAs have been characterized in myogenesis.…”
Section: Introductionmentioning
confidence: 99%